2017
DOI: 10.18203/2320-6012.ijrms20175721
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of older adults in a community in Pathanamthitta district of Kerala

Abstract: Background: India is said to be shifting from an undernourished to over nourished population with advances in health, economy and medical care. But there is paucity of information regarding nutritional status of older adults in the country, who are socially and economically insecure. Hence the present study attempts to assess the nutritional status of people above 60 years of age, and to find the factors associated with it.Methods: A cross sectional study was conducted among 129 people aged above 60 years, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Deprived nutritional status as indicated by lower calf circumference is another problem among rural older adults with lower SES. Poor transportation facilities in the rural area is one of the barriers for access to food items, thus increasing dependency on locally available resources for their daily intake to save cost [42]. Progressive decline in muscle mass or lean tissue may lead sarcopenia and further deterioration in physical health [43].…”
Section: Discussionmentioning
confidence: 99%
“…Deprived nutritional status as indicated by lower calf circumference is another problem among rural older adults with lower SES. Poor transportation facilities in the rural area is one of the barriers for access to food items, thus increasing dependency on locally available resources for their daily intake to save cost [42]. Progressive decline in muscle mass or lean tissue may lead sarcopenia and further deterioration in physical health [43].…”
Section: Discussionmentioning
confidence: 99%
“…13,32 Total rural sample was 3500 with ranging from 80 to 545. 9,30 The overall prevalence of malnutrition among the rural elderly was found by meta-analysis was 21.67% (95% CI: 16.44-27.40).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies indicated educational status was a crucial risk factor for malnutrition. 9,12,16,20,[23][24][25][26]31 Illiteracy is extremely related to elderly malnutrition and supported by study of Baweja et al 50 Lack of education diminishes the consideration in regards to sound way of life, optimum diet which can attribute to individual nutritional status. Elderly having higher education, owing to their exposure to the outside world, are more aware of personal hygiene, curative health care than that of less educated elderly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations